Aceh Provincial Drug Abuse Rehabilitation Center with the Therapeutic Community Approach - Nuri Ihsani (Jurnal Ilmiah Mahasiswa Arsitektur dan Perencanaan, 2019)
Aceh provincial drugs rehabilitation center is a facility dedicated to rehabilitate victims of drug abuse. In this place the victims will be restored both physically and psychologically to recover from addiction and return to society. There are two methods of rehabilitation process, medical rehabilitation and social rehabilitation. Each method requires different facilities. Medical rehabilitation is a medical treatment by providing therapy and medication. Whereas social rehabilitation is a process of rehabilitation by restoring the psychological well-being of the victim and exercising their ability to return and work in the community normally. As a place of rehabilitation, this area must be able to adjust the behavior of victims of drug abuse as users with the design applied. This is a consideration of the reasons for choosing a behavior architecture theme in this design. This theme aims to create a safe rehabilitation area and help the recovery process to run optimally.